Feed resources for ruminants in smallholder farming systems in Southeast Asia - Pezo, Danilo A.; Lanting, E.F.; Chee, W.C.; Kerridge, Peter C. (Australian Centre for International Agricultural Research, 2000)
The demand for meat and milk in Southeast Asia has almost doubled in the past two decades, and this trend is expected to continue in following years. There is a need to enhance productivity in the prevalent smallholder crop animal systems, in order to match these increases in demand without jeopardising the natural resource base. Some estimates suggest that available roughages may be enough to sustain the actual livestock population, but better quality and high yielding improved forages, and other nutritional options are needed to ensure more efficient use of available roughages. Current options for improving the efficiency of feeding systems in smallholder livestock farms include: a) appropriate budgeting of available feed resources; b) greater use of improved forages; c) supplementation of low quality feed resources; and d) treatment of crop residues. Research on genetic improvement of crop residues and the manipulation of rumen microbial populations should provide new options for the medium to long term.